Economic growth and the public deficit in EU member states in Central and Eastern Europe - Bettina Bökemeier (Romanian Journal of Fiscal Policy (RJFP), 2015)
This paper studies the determinants of economic growth and the role of the public budget in European Union (EU) member states in Central and Eastern Europe, that joined the European Union in 2004, with a balanced data set from 1996 until 2012. A special focus is set on the relationship between growth and the public deficit and their behavior before and after the accession is studied. The outcome reveals a significant negative relationship between the deficit ratio and subsequent economic growth for the group of the eight selected countries. This effect indicates to be stronger after EU accession than before.
Keywords: H62; E62; O40; 330; economic growth; public debt; new EU member states